2005
DOI: 10.1183/09031936.04.00095804
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle dysfunction in idiopathic pulmonary arterial hypertension

Abstract: Idiopathic pulmonary arterial hypertension (IPAH) is a pulmonary vasculopathy of unknown aetiology. Dyspnoea, peripheral airway obstruction and inefficient ventilation are common in IPAH. Data on respiratory muscle function are lacking.This prospective single-centre study included 26 female and 11 male patients with IPAH in World Health Organization functional classes II-IV. Mean¡SD pulmonary artery pressure was 48.6¡16.9 in females and 53.1¡22.9 mmHg in males; cardiac output was 3.7¡1.3 and 4.2¡1.7 L?min -1 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
2
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 41 publications
12
146
2
10
Order By: Relevance
“…The combination of alveolar hyperventilation and increased (parallel) dead space ventilation is remarkable as it puts an extra ventilatory drive on an already increased effort of breathing. These findings are in unison with reports in patients with iPAH (Meyer et al, 2005;Wessel et al, 1964;Zoia et al, 2002). The alveolar hyperventilation seemed to be only in part hypoxic driven, as administration of 100% oxygen for at least 20 minutes increased but did not normalize Pa,CO 2 (4.50 ± 0.42 kPa vs. 4.58 ± 0.42 kPa).…”
Section: Pathophysiology Of Dyspnea In Ctephsupporting
confidence: 75%
See 2 more Smart Citations
“…The combination of alveolar hyperventilation and increased (parallel) dead space ventilation is remarkable as it puts an extra ventilatory drive on an already increased effort of breathing. These findings are in unison with reports in patients with iPAH (Meyer et al, 2005;Wessel et al, 1964;Zoia et al, 2002). The alveolar hyperventilation seemed to be only in part hypoxic driven, as administration of 100% oxygen for at least 20 minutes increased but did not normalize Pa,CO 2 (4.50 ± 0.42 kPa vs. 4.58 ± 0.42 kPa).…”
Section: Pathophysiology Of Dyspnea In Ctephsupporting
confidence: 75%
“…In COPD and chronic (left) heart failure multiple mechanisms have been suggested to be involved in reduced muscle strength; changes in muscle fibre type ratio, abnormal intracellular Ca 2+ profile, impaired muscle perfusion, decreased number of mitochondria, decreased oxidative enzymes, electrolyte disturbance, steroid therapy, malnutrition, wasting and cardiac cachexia. Most of these mechanisms do not seem to apply in PH (Meyer et al, 2005). However, we observed an increase in body mass index (BMI) one year after PEA in patients with CTEPH; in 48 consecutive CTEPH patients the BMI increased from 29.7±5.6 preoperatively to 30.8±5.7 at 1 year after surgery (p=0.001).…”
Section: Future Researchmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, a prospective study of 20 control patients and 37 patients with idiopathic PH (class II-IV, 26 women and 11 men) revealed that the patients with PH had lower values for PImax and PEmax, as well as weakness in the inspiratory and expiratory musculature 10 . These patients may hyperventilate during rest, exercise, and sleep, which can cause increased respiratory muscle activity, overload the inspiratory musculature, and lead to muscular weakness.…”
Section: Tablementioning
confidence: 99%
“…[1][2][3] This decrease in the static elastic recoil of the lungs is related to changes in the quantity and composition of the supporting structures within the lung parenchyma. 4 The reduced physiological capacity of the respiratory system with aging can predispose vulnerable individuals to an increased risk for respiratory diseases, such as respiratory insufficiency, atelectasis, and respiratory infection. 5,6 Some breathing exercises are commonly used in the treat-ment and prevention of aging-related respiratory conditions.…”
Section: Introductionmentioning
confidence: 99%